2022
DOI: 10.1101/2022.01.31.478213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian disruption enhances HSF1 signaling and tumorigenesis in Kras-driven lung cancer

Abstract: Disrupted circadian rhythmicity is a prominent feature of modern society and has been designated as a probable carcinogen by the World Health Organization. However, the biological mechanisms that connect circadian disruption and cancer risk remain largely undefined. We demonstrate that exposure to chronic circadian disruption (chronic jetlag, CJL) increases tumor formation in a mouse model of KRAS-driven lung cancer. Molecular characterization of tumors and tumor-bearing lung tissues revealed that CJL enhance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Circadian disorder assessed by CCD has previously been used to infer disruption of circadian rhythms [106]. Indeed, we observed that genetic disruption of circadian rhythms by BMAL1 KO resulted in a disordered clock, as observed in peritoneal macrophages (Figure 6B).…”
Section: Heterogeneity Of Circadian Rhythms Within a Population Can U...mentioning
confidence: 59%
“…Circadian disorder assessed by CCD has previously been used to infer disruption of circadian rhythms [106]. Indeed, we observed that genetic disruption of circadian rhythms by BMAL1 KO resulted in a disordered clock, as observed in peritoneal macrophages (Figure 6B).…”
Section: Heterogeneity Of Circadian Rhythms Within a Population Can U...mentioning
confidence: 59%
“…More notably, our findings suggest that MYC "releases" biosynthetic and metabolic processes from circadian control in order to be upregulated without regards to oscillation. However, the molecular circadian clock is not disrupted in all cancers, and in particular seems to be maintained (albeit in an altered state) in those driven by mutated HRAS or KRAS [72][73][74]. In fact, alteration (but not complete ablation) of the circadian clock may enhance MYC expression even in cases where MYC is not amplified, and MYC itself is circadian-regulated and oscillatory in these settings [12,17,[75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, researchers have shown that the master clock activators BMAL1 and CLOCK have anti-apoptotic roles, promoting liver cell proliferation through the cell cycle regulator Wee-140 63 . On the other hand, oncogenes such as c-MYC or KRAS interfere with circadian pacemaking 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…In yeast and mammals, evolutionary pressures acted to gate DNA replication and cell division, shielding the dividing cell from solar radiation and toxic metabolites 12,17,18 . The cell cycle and circadian clocks share components and signaling molecules and show reciprocal regulation [19][20][21][22][23][24] . In addition, several oncogenes have been causally linked to circadian clock dysfunctions and may directly hijack clock mechanisms 22,25 .…”
Section: Introductionmentioning
confidence: 99%